"If You Don't Believe that You're Doing Some Good with the Work that You Do, then You Shouldn't Be Doing It": An Interview with Cindy Selfe. - Bailie, Brian (Composition Forum)
In this interview, Cindy Selfe talks about the intersections of technological literacy, digital scholarship, poststructuralist theory, and university politics. In doing so, she provides a lens for scholars trying to understand the milieu of the university by viewing its potential in juxtaposition to its past; explains how technology redefines the boundary between theory and experiential reality; and recommends a set of simple questions digital scholars can ask themselves when attempting to create localized, sustainable tactics demonstrating their work has the reach and scope of their immediate non-digital peers.